Real convergence of EU member states - evaluation attempt = Konwergencja realna krajów UE - próba oceny - Grzelak, Aleksander; Kujaczyńska, Marlena (Zielona Góra: Faculty of Economics and Management Press)
The key aim of the article is to verify the hypothesis concerning convergence in the economic development of the EU member states, which is reflected in evening out differences in the economic development level of the EU member states. New member states develop faster than old member states. In the light of the presented results, economic convergence of the member states seems not to be homogenous. Thus, it can be provisionally stated that progress has been recorded as regards convergence of the member states economies, in particular since 2007, although it needs to be emphasised that differences between them are still significant.
Keywords: konwergencja; Unia Europejska; wzrost gospodarczy; convergence; UE; economic growth